Comparative Analysis of Language Style and Religious Values in the Text of Mahallul Qiyam Kitab Maulid Ad-Diba'i: A Stylistic Study - Rezky Latifah Nuraida; Rohanda; Mohamad Syasi (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to analyze the use of comparative language styles in the Mahallul Qiyam text contained in the book Majmu'atul Maulid Wal Ad'iyah written by Imam Abdurrahman al-Diba'i and the religious values ??contained therein. As an approach, this study uses a stylistic approach with the applied method being a qualitative descriptive method. The main focus of this study includes the types of comparative language styles and also the religious values contained therein. The data sources in this study are verses in the Mahallul Qiyam text that contain elements of comparative language styles. The data collection technique is carried out through the listening and speaking technique with intensive reading of the text, while for data analysis, the distribution method is carried out through the direct element (BUL) technique to identify the tenor, vehicle, and meaning relationship. The results of the study indicate that there are comparative language styles such as tasybih, majaz, and personification. The application of these language styles not only plays a role as an aesthetic element, but also as a tool to convey religious values. Among the most prominent religious values are the values of faith, which relate to belief in the nobility of the Prophet Muhammad (peace be upon him), and the values of morality and worship, which are part of its spiritual implications. Thus, the text of Mahallul Qiyam reflects the blend of linguistic beauty and profound religious meaning within the Islamic literary tradition.